Work From Anywhere dan Transformasi Relasi dalam Keluarga Modern - Ainul Zulqoifah Asmawati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This integrative review examines how work from anywhere (WFA) transforms modern family relations. Peer-reviewed studies on remote work, work-family boundaries, gendered household labor, parenting, and couple dynamics were synthesized, mainly from 2016-2025. Findings reveal a flexibility paradox. Reduced commuting and greater autonomy may increase family time, paternal involvement, and cooperative role-sharing. Yet overlapping work and home can intensify interruptions, extended availability, technostress, spatial conflict, and unequal care burdens. Outcomes depend on boundary control, workload, housing, childcare, gender norms, and organizational support. WFA should therefore be treated as a negotiated family arrangement, not only an individual employment benefit. Sustainable practice requires explicit household agreements, family-supportive work design, equitable care, and protected disconnection.